EFEKTIVITAS JOBSHEET PADA MATA DIKLAT INSTALASI LISTRIK BANGUNAN SEDERHANA KELAS X PROGRAM KEAHLIAN TEKNIK INSTALASI TENAGA LISTRIK DI SMK N 3 SEMARANG - Sari, Ika Anjar Kumala (Electrical Engineering, Universitas Negeri Semarang, 2014)
The purpose of this study was to determine the Effectiveness and to know level of effectiveness jobsheet on The Simple Building Electrical Installation Subject at Vocational High School 3 Semarang. The research using purposive sampling technique with First Class Installation of Electric Power Engineering Program at SMKN 3 Semarang year 2012/2013 with a population sample of 36 students. Data were analyzed using descriptive analysis. The result showed that the effectiveness of mastery learning aspect of the increase in value of the average student before using jobsheet 69,5(<KKM=74) after using jobsheet 88,16(>KKM) with the initial percentage of 72% (not yet complete) become 100%(complete). Completeness results of this study followed the results of effectiveness of the aspect student’s activity by 83%(effective) and the achievement of student’s motivation by 85,7%(very high level of motivation). Based on the above results, it can be concluded that the effective by used jobsheet on the simple building electrical installation is effective to be applied to The Simple Building Electrical Installation Subject for First Class Installation of Electric Power Engineering Program at Vocational High School 3 Semarang. This is known from the three indicators of effectiveness used jobsheet are the complete student’s learning outcome, the effectiveness of students activities and student motivation.